PENDIDIKAN DAN KESEMPATAN KERJA BAGI PEREMPUAN TERHADAP TINGKAT FERTILITAS DI KOTA GORONTALO - Syamsul Syamsul (Lembaga Penelitian dan Publikasi Nobel Indonesia, 2018)
As well as the differences that occur in developing countries and developed countries, where birth rates in many developing countries today is higher than the birth rate in developed countries (Western Europe in the pre-industrial). This happens because women in developing countries tend to marry at the age easier. As a result, more number of families in certain age and population groups over the duration of childbearing age to give birth this anak.Penelitian aims to determine how the relationship between education and employment opportunities for women at the level of the birth rate (fertility) in Gorontalo. The data used are primary data and secondary data. The study was conducted in the city of Gorontalo. The analysis unit used is the analysis of Chi-Square (X2).Research shows that there is a relationship between the educational opportunities for women in the birth rate (fertility) with a level of relations that are moderate (moderate). There is a relationship between employment opportunities for women in the birth rate (fertility) level of relations that are weak. Provide opportunities for women to pursue higher education may reduce fertility rates. Women who work, particularly in the formal sector to reduce the level of fertility.